Inhibition of TRPA1 Attenuates Oxidative Stress-induced Damage After Traumatic Brain Injury via the ERK/AKT Signaling Pathway. (1st July 2022) - Yang, Xin-Jie; Ling, Shizhang; Zhou, Meng-Liang; Deng, Hong-Ji; Qi, Min; Liu, Xi-Lin; Zhen, Cheng; Chen, Yun-Xiao; Fan, Xi-Ran; Wu, Ze-Yu; Ma, Feng-Chun; Rong, Jun; et al.
Highlights: Traumatic brain injury features Ca 2+ /reactive oxidative species-related apoptosis. Traumatic brain injury was modeled in vitro and in vivo. Traumatic brain injury upregulated TRPA1 expression via Nrf2. TRPA1 inhibition reduced apoptosis partly via CaMKII/AKT/ERK signaling. Blockade of TRPA1 might be developed as a treatment for traumatic brain injury. Abstract: Neuron apoptosis is a feature of secondary injury after traumatic brain injury (TBI). Evidence implies that excess calcium (Ca 2+ ) ions and reactive oxidative species (ROS) play critical roles in apoptosis. In reaction to increased ROS, the anti-oxidative master transcription factor, Transient receptor potential Ankyrin 1 (TRPA1) allows Ca 2+ ions to enter cells. However, the effect of TBI on the expression of TRPA1 and the role of TRPA1 in TBI are unclear. In the present study, TBI in the mouse brain was simulated using the weight-drop model. The process of neuronal oxidative stress was simulated in HT22 neuronal cells by treatment with hydrogen peroxide. We found that TRPA1 was significantly upregulated in neurons at 24 h after TBI. Neuronal apoptosis was increased in the in vivo and in vitro models; however, this increase was reduced by the functional inhibition of TRPA1 in both models. After TBI, TRPA1 was upregulated via nuclear factor, erythroid 2 like 2 (Nrf2) in neurons. TRPA1-mediated neuronal apoptosis after TBI might be achieved in part through the CaMKII/AKT/ERK signaling pathway. To sum up, TBI-triggered TRPA1 upregulation in neurons is mediated by Nrf2 and the functional blockade of TRPA1 attenuates neuronal apoptosis and improves neuronal dysfunction, partially mediated through the activation of the calcium/calmodulin dependent protein kinase II (CaMKII) extracellular regulated kinase (ERK)/protein kinase B (AKT) signaling pathway. Our results suggest that functional blockade of TRPA1 might be a promising therapeutic intervention related to ROS and Nrf2 in TBI.